Stereoselective Synthesis of 1, 2‐trans‐Diamines Using the Three‐Component Borono‐Mannich Condensation – Reaction Scope and Mechanistic Insights. Issue 14 (13th April 2017) - Norsikian, Stéphanie; Beretta, Margaux; Cannillo, Alexandre; Auvray, Marie; Martin, Amélie; Retailleau, Pascal; Iorga, Bogdan I.; Beau, Jean‐Marie
Abstract : The Petasis borono‐Mannich (PBM) process with easily accessible N ‐protected α‐amino aldehydes produces 1, 2‐ trans ‐diamines diastereoselectively with an enantiomeric excess up to 98 %. The protecting group on the nitrogen atom had a decisive influence on both the yield and the enantiomeric purity of the condensation products, and the best results were obtained with sulfonamide derivatives [nosyl (Ns), tosyl (Ts), and mesyl (Ms)]. To get a better understanding of the influence of the protecting group, we investigated the mechanism of the borono‐Mannich reaction through DFT calculations. Abstract : N ‐Nosylated α‐amino aldehydes generate 1, 2‐ trans ‐diamines diastereoselectively with an enantiomeric excess of up to 98 % through the Petasis borono‐Mannich three‐component condensation.